Training to Improve The Skills and Professionalism of Museum Tour Guides in Mojokerto, East Java - Rizki Adityaji; Agoes Tinus Lis Indrianto; Agustinus Nugroho; Adrie Oktavio; Hendra (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
Mojokerto, a city in East Java rich in history and culture, has a number of fascinating museums. These museums are silent witnesses to the glory of the past and a window for us to peek into the civilization that has developed in the land of Java. Mojokerto is known for its rich cultural heritage and history, but its potential as a tourist destination is still underutilized due to the lack of quantity and quality of skilled museum guides. With a better visiting experience, organized and informative narratives, it is hoped that more people will be interested in visiting museums in Mojokerto and participating in supporting the preservation of the history and culture of the Indonesian nation. This PKM uses in-depth interviews with 10 museum guides who have undergone training and informant observations of training activities and their implementation in the field. The findings in this PKM activity show a significant increase in guide skills, historical knowledge, and visitor guiding techniques, resulting in a better visitor experience in the museum. This PKM ends with recommendations to improve community service programs aimed at developing local human resources in sustainable heritage tourism. This PKM examines the impact of community service initiatives organized by lecturers at Ciputra University Surabaya, with a focus on museum guide training in Mojokerto, East Java.